Pertumbuhan dan Produksi Tanaman Kedelai Edamame pada Berbagai Dosis Inokulan dan Jenis Pupuk Kandang: Growth and Production of Edamame Soybean Plants at Various Doses of Inoculants and Types of Manure - Manudji, Aulia Putry Lestari Manudji; Syafar, Rahman; Julia, As (Fakultas Pertanian Universitas Islam Makassar, 2025)
This study aimed to determine the effect of the best inoculant doses and manure doses on the growth and production of edamame soybean plants. This study was conducted at the Makassar Village and Transmigration Community Empowerment Training Center which lasted for three months, from August to October 2024. This study was conducted in the form of a two-factor factorial Randomized Block Design (RBD) experiment. The first factor was the dose of pure culture inoculant with 3 levels, namely 10 grams/kg of seed, 20 grams/kg of seed and 30 grams/kg of seed. While the second factor was the dose of Chicken, Cow and Goat manure with a dose of 6 kg/plot each. Based on the results of the study, the inoculant dose of 20 grams/kg of seed gave a better effect on plant height 14 HST (25.4 cm), plant height 21 HST (38.7 cm), fresh pod weight per plant (90.6 g), fresh pod weight per plot (1.1 kg) and production tons/ha (5.5 tons/ha). Goat manure with a dose of 6 kg/plot gave a good effect on plant height 14 HST (25.5 cm), plant height 21 HST (36.6 cm), fresh weight of pods per plant (80.6 g), fresh weight of root nodules (1.1 g), fresh weight of pods per plot (1.0 kg) and production tons/ha (5.1 tons/ha). Then there was no interaction between the dose of inoculant and various manures used on the growth of edamame soybean production.